Having Goal May Not Motivate an Individual – Case Study - Dr. Yogesh S. Daudkhane (International Journal of Engineering and Management Research, 2019)
Goals are anticipated positive future states or events which a person strives to achieve. The terms aim, objective, and standard are widely used synonymously. Other related concepts, however, like intention, norm, and task can be distinguished from goals because they emphasize the action itself rather than the anticipated future state. The importance of a goal for motivated action is beyond doubt. Action theories, for instance, use goal as the key element for defining action—their object of interest. Many motivation theories also see goals as key elements and illustrate their motivational effect with a metaphor: The goal ―pulls‖ the action. Goals are seen as an effective means for promoting motivation and are therefore used as an instrument for leading and motivating people. Locke and Latham’s (1990) goal-setting theory is based on the assumption that the motivational effects of performance goals mainly determine a person’s performance on work-related tasks. An application of this notion can be seen in Management by Objectives (MBO), a popular leadership method that aims at transforming a company’s strategic goals into individual goals. It is expected that inasmuch as an employee accepts and adopts the negotiated goals, he or she will be better oriented and more motivated than without a goal. Nevertheless, if we are to explain motivation, it is not sufficient to study the goal and its features alone. It is important to additionally consider the characteristics of the person, since the value and motivating power of a given goal depends heavily on the specific needs of the person. Kehr’s (2004b) compensatory model of work motivation and volition, for instance, states that a goal should match the person’s basic needs and motives in order to be motivating. To complicate the issue further, some related approaches emphasize that a goal should also fit in with the other goals for which the person strives. By discussing the aforementioned approaches, this research-paper will highlight the motivating potential of goals but also explain why goals may sometimes also lose their motivating force. To introduce the topic and to bridge the gap between theory and practice, we will begin by presenting a case study. The case starts by introducing Lokesh, the character, who has a goal. We would therefore expect him to be highly motivated to pursue his goal. Alas, Lokesh feels thoroughly demotivated. What could be the reasons for the lack of motivating power of Lokesh’s goal? To develop possible answers to this question, the researcher will scrutinize Lokesh’s situation more closely, and by referring to various theoretical frameworks, the paper will illustrate various conditions under which goals can lose their motivating potential. Our line of argument will proceed as follows: We will begin by focusing on Lokesh’s salient goal and investigate the characteristics of this goal. Next, we will include other pre-existing goals, which will enable us to discuss the potentially complex network into which Lokesh’s prevalent goal may be integrated. We will then examine some specific goal relevant characteristics of the person: motive dispositions and volitional strength. As a final step of our analysis, we intend to broaden the view to include potentially relevant situational aspects. As a tentative solution to Lokesh’s problem, we will present two alternative sources of motivation: incentives that result from performing the activity itself and visions.